The effect of maternal parameters on umbilical artery blood gas values and neonatal well-being in singleton pregnancies - Bilgin, Huseyin; Kosus, Aydin; Kosus, Nermin; Kara, Semra; Eren, Abdulkadir; Hizli, Deniz (The European Research Journal, 2016)
Background. Umbilical cord blood analysis for assessment of the newborn’s acid-base status soon after birth is the most objective way of evaluating the fetal metabolic condition at delivery. We researched the effects of maternal age, multiple gestation, fetal heart rate, gestational age, parity, delivery mode and total duration of labor on fetal well-being as assessed by umbilical cord blood gas parameters. Methods. Prospective study conducted on 67 singleton pregnant women and their off-spring. Maternal age, multiple gestation, fetal heart rate (FHR), gestational age, parity, delivery mode and total duration of labor were recorded. Umbilical artery blood samples were collected at birth. A blood gas analysis was performed on each collected sample. The relationship between maternal parameters and umbilical cord arterial blood gas were investigated. Results. We found positive correlation between pH and gravida and parity (p=0.026, p=0.049, respectively), whereas negative correlation between total duration of labor and O2 saturation (p=0.033). Base deficit was negatively correlated with gravida and parity (p=0.025, p=0.011, respectively). In linear regression models, FHR and gravida were a significant predictor of pH value (p=0.029 and p=0.040, respectively). Conclusions. We found no association between maternal age, gestational age, gravida, parity and duration of labor and neonatal acidemia. Thus, maternal age, gestational age, gravida, parity and duration of labor may not be at increased risk of perinatal morbidity. However, the elevation of FHR was related with an increased risk of neonatal morbidity.